Pengaruh Komunikasi Pemasaran Terhadap Citra Perusahaan PT. Telkom Indonesia Manado - Papeo, Adyan; Kalangi, Johny A. F; Punuindoong, Anneke Y. (Sam Ratulangi University, 2018)
This research is based on the existing phenomenon that is the influence of marketing communications to the image perusuhaan. The purpose of the research is to know whether marketing communications can affect in the formation of corporate image and the object of this research is PT. Telkom Indonesia Manado. Penelitian ini bertujuan untuk menjawab permasalahan atau fenomena yang disebutkan diatas.Â Penelitian ini merupakan penelitian deskriptif kuantitatif dengan jumlah sampel sebnayak 130 responden. Dalam penelitian ini menngunakan dua variabel yang terdiri dari variabel bebas yaitu (komunikasi pemasaran) dan varibel terkait yaitu (citra perusahaan). Pengujian instrument menggunakan uji validitas, dan uji realibitas, sedangkan metode analisis menggunakan analisis regresi linier berganda dengan uji t, uji f dan koefisien determinated R Square. In the calculation of multiple linear regression using SPSS verssi 20 software, the results of t test analysis show the variables Advertising, Sales Promotion, Public Relations, Personal Selling and Direct Selling partially affect the image of the company and highlighted significant. So it can be concluded that the variables Advertising, Sales Promotion, Public Relation, Personal Selling, and Direct Selling jointly have a contribution influence on corporate image with the number of percentage of 0.126 or 12.6%. So means the level of Influence komunikasai Marketing of Corporate Image PT. Telkom Indonesia Manado stated low while 88.4 is a factor that is not researched by researchers.Â Keywords: Marketing Communication, Corporate Image